2003
DOI: 10.1002/jmv.10428
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hepatitis B virus genotypes on the development of preS deletions and advanced liver disease

Abstract: Hepatitis B virus (HBV) mutants with deletions in the preS region have not been evaluated for association with viral genotypes. In a case-control study, HBV DNA samples collected from 80 each of carriers infected with HBV genotype B or C were examined for preS deletions. PreS deletion mutants were found in a total of 37 of 160 (23%) HBV carriers. Carriers with preS deletion mutants were older (56.0 +/- 12.7 vs 49.3 +/- 16.9 years, P < 0.05), were infected more frequently with HBV genotype C (84% vs 40%, P < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
118
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(129 citation statements)
references
References 37 publications
(59 reference statements)
9
118
2
Order By: Relevance
“…Our study showed a significantly higher rate of pre-S2 deletions in the children of the HCC group than in the group with chronic HBV infection. The meaning of our results is unique and not merely in agreement with the studies in adults, because we found that pre-S2 deletions in HBV genomes did not necessarily take decades to accumulate, as in adult patients with advanced liver diseases (1,(15)(16)(17)(18)(19)(20)(21)(22); they emerged in nearly half of the young children with HBV-related HCC that developed in a relatively short period of time.…”
Section: Discussionsupporting
confidence: 68%
“…Our study showed a significantly higher rate of pre-S2 deletions in the children of the HCC group than in the group with chronic HBV infection. The meaning of our results is unique and not merely in agreement with the studies in adults, because we found that pre-S2 deletions in HBV genomes did not necessarily take decades to accumulate, as in adult patients with advanced liver diseases (1,(15)(16)(17)(18)(19)(20)(21)(22); they emerged in nearly half of the young children with HBV-related HCC that developed in a relatively short period of time.…”
Section: Discussionsupporting
confidence: 68%
“…4) when a part of the CURS/CP of the wild-type HBV/E replication clone was replaced by the HNF1 binding tandem repeat of UK2. Pre-S deletion is observed in cases of long-lasting HBV chronic infection and advanced liver diseases (27,37). As the positions and lengths of pre-S deletions differ in each case, their effects on HBV replication have not been clearly elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The deletion over pre-S gene may affect the expression of middle and small surface proteins, resulting in intracellular accumulation of large surface protein [86], and contribute to more progressive liver cell damage and finally hepatocarcinogenesis [87,88]. In our recent case-control study, pre-S deletion mutant of HBV were determined in 202 asymptomatic carriers and 64 HCC patients with chronic HBV genotype B or C infection.…”
Section: Naturally Occurring Mutantsmentioning
confidence: 99%